Language Acquisition On Children Through Singing In Gunungkidul - Rochmat Budi Santosa; Novianni Anggraini; Fithriyah Nurul Hidayati; Rindiani Rindiani (Universitas Bengkulu, 2022)
Language acquisition is an unconscious process in understanding and learning language. In general, language acquisition occurs in children through exposure to those around them. One effective exposure for language acquisition is through song. This study aims to identify the role of using the singing method for language acquisition in early childhood, be it phonological, morphological, or syntactic acquisition. This research is qualitative research with naturalistic techniques. The data collection used in-depth observation and interviews. The sample of this research is the students of Early Childhood Education (PAUD) Nur Insani, Piyaman, Wonosari, Gunungkidul who are 3-4 years old. The results showed that by using the singing method, students were able to: a) acquire several phonemes and even some were able to distinguish these phonemes, b) use suffixes, and c) express simple declarative, imperative, and interrogative sentences.